Astrocytes render memory flexible by releasing D-serine and regulating NMDAR tone in the hippocampus - 고우현; PARK, MI JEONG; Chun, Ye eun; Lee, Jae kwang; 심현수; Mingu Gordon Park; kim, sun pil; Moonsun Sa; Jinhyeong Joo; Hyunji Kang; 오수진; Woo, Jun Sung; et al. (Elsevier BV, 2022)
Background: NMDA receptor (NMDAR) hypofunction has been implicated in several psychiatric disorders with impairment of cognitive flexibility. However, the molecular mechanism of how NMDAR hypofunction with decreased NMDAR tone causes the impairment of cognitive flexibility has been minimally understood. Furthermore, it has been unclear whether hippocampal astrocytes regulate NMDAR tone and cognitive flexibility. Methods: We employed cell type？specific genetic manipulations, ex vivo electrophysiological recordings, sniffer patch recordings, cutting-edge biosensor for norepinephrine, and behavioral assays to investigate whether astrocytes can regulate NMDAR tone by releasing D-serine and glutamate. Subsequently, we further investigated the role of NMDAR tone in heterosynaptic long-term depression, metaplasticity, and cognitive flexibility. Results: We found that hippocampal astrocytes regulate NMDAR tone via BEST1-mediated corelease of D-serine and glutamate. Best1 knockout mice exhibited reduced NMDAR tone and impairments of homosynaptic and α1 adrenergic receptor？dependent heterosynaptic long-term depression, which leads to defects in metaplasticity and cognitive flexibility. These impairments in Best1 knockout mice can be rescued by hippocampal astrocyte-specific BEST1 expression or enhanced NMDAR tone through D-serine supplement. D-serine injection in Best1 knockout mice during initial learning rescues subsequent reversal learning. Conclusions: These findings indicate that NMDAR tone during initial learning is important for subsequent learning, and hippocampal NMDAR tone regulated by astrocytic BEST1 is critical for heterosynaptic long-term depression, metaplasticity, and cognitive flexibility. ？ 2021 Society of Biological Psychiatry